2020
DOI: 10.1002/jum.15581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Machine Settings on Ultrasound Assessment of B‐lines

Abstract: Objectives-B-lines are a lung ultrasound (LUS) artifact that often indicate pathology. Little is known about the optimal ultrasound machine settings to assess B-lines. We compared settings typically used to evaluate B-lines at our institution with adjusted settings based on recent studies.Methods-In order to determine typical settings for B-line assessment, we retrospectively reviewed LUS images obtained at our institution. We then prospectively performed LUS with both typical and adjusted settings, using curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
(63 reference statements)
1
26
0
2
Order By: Relevance
“…51 (28%) patients in the interventional arm died versus 59 (33%) in the usual care group (HR 0.99; 95% CI 0.61 -1.29). Despite not meeting the target enrollment, the study demonstrated reduction in B-line score in the intervention arm from a baseline of 15 B-lines on enrollment (95% CI 12-19) to 9 at study end (95% CI 5-12) compared with those in the control arm who had worsening pulmonary congestion with baseline B-line score of 16 (95% CI [13][14][15][16][17][18][19][20] rising to 30 at study end (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. While there were no differences in pre-or post-dialysis blood pressures or left-ventricular mass index, ambulatory blood pressure monitoring was not undertaken as in the study by Loutradis.…”
Section: Interventional Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…51 (28%) patients in the interventional arm died versus 59 (33%) in the usual care group (HR 0.99; 95% CI 0.61 -1.29). Despite not meeting the target enrollment, the study demonstrated reduction in B-line score in the intervention arm from a baseline of 15 B-lines on enrollment (95% CI 12-19) to 9 at study end (95% CI 5-12) compared with those in the control arm who had worsening pulmonary congestion with baseline B-line score of 16 (95% CI [13][14][15][16][17][18][19][20] rising to 30 at study end (95% CI [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. While there were no differences in pre-or post-dialysis blood pressures or left-ventricular mass index, ambulatory blood pressure monitoring was not undertaken as in the study by Loutradis.…”
Section: Interventional Studiesmentioning
confidence: 93%
“…15 Any transducer can be used, but the most optimal images are captured when the focal depth is set at the pleural line with increasing gain in the far field and harmonics turned off. 16 Quantitative lung ultrasound is predictive of acute cardiogenic pulmonary edema in the emergency department and outperforming the physical exam and even chest x-ray. 8,17 Lung ultrasound is also sensitive for the presence of pleural effusions which appear as anechoic structures which allow passage of the ultrasound beam and interdigitate between lung and diaphragm [Figure 3] .…”
Section: Technical Aspectsmentioning
confidence: 99%
“…In sector and curvilinear transducers, multiple B-lines spread radially, whereas in linear probes, multiple B-lines run in parallel (Figure 10). Many published studies did not mention the presets or used a variety of presets, including cardiac, abdominal, and lung presets set by the manufacturers [9,31,32]; thus, the results should be cautiously interpreted when the performance is compared between the types of transducers. Smit et al assessed the concordance between a broadband linear transducer (12-4 MHz) and a sector transducer (4-1 MHz) of a handheld ultrasound device in the assessment of lung aeration using B-lines in mechanically ventilated intensive care unit patients.…”
Section: Selection Of Transducersmentioning
confidence: 99%
“…However, the mechanisms underlying the vertical artifacts in cardiogenic pulmonary edema have not been fully elucidated. Furthermore, there is no international consensus with regard to the optimal settings of ultrasound machines even though their contribution to the configuration of vertical artifacts is evident [ 7 , 8 , 9 ]. They may affect the diagnostic accuracy inappropriately [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Harmonics can decrease the reverberation which is the key reason results in the A-lines and B-lines.When using harmonics,the A-line and B-line are weakened compared with using fundamental frequency,meanwhile, because of higher frequency,the attenuation in the far field increased even though the image looks very fine [33,34].Therefore,it is recommended to use fundamental frequency when performing neonatal LUS in most cases (Figures 7 and 8).…”
Section: Fundamental Frequency Imagingmentioning
confidence: 99%